Exploring the Nexus Between Economic Crisis and Family Instability Among Female Teachers in Zimbabwe - Chikunda, Plaxcedes; Ingwani, Viola (International Journal For Research In Educational Studies, 2018)
The study explores family instability as a social problem affecting female teachers due to the economic crisis prevailing in Zimbabwe. The research was designed and conducted within the qualitative paradigm. The methodology involved informal conversational interviews and focus group discussions. The study was conducted with a group of thirty female teachers who were pursuing their master of education studies. The study established that female block release students experience social problems such as family instability as a result of the economic hardships that they find themselves in.